The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2001
DOI: 10.1128/aem.67.2.646-653.2001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Pathogenic Potential ofListeria monocytogenesIsolates from the Smoked Fish Industry

Abstract: This study was designed to evaluate the hypothesis that some of the Listeria monocytogenes subtypes associated with foods, specifically smoked fish, may have an attenuated ability to cause human disease. We tested this hypothesis by using two different approaches: (i) comparison of molecular subtypes found among 117 isolates from smoked fish, raw materials, fish in process, and processing environments with subtypes found among a collection of 275 human clinical isolates and (ii) the evaluation of the cytopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
83
0
5

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 37 publications
7
83
0
5
Order By: Relevance
“…A previous study reported isolation of L. monocytogenes from cow stools, carcasses and meat products, and suggested that feces was the most likely source of contamination of the carcasses [3]. The pathogen has also been isolated from environments such as slaughterhouses and sewage, sludge and food-processing plants [4,8,9]. These reports suggest the presence of various sources of L. monocytogenes contamination in the environment.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…A previous study reported isolation of L. monocytogenes from cow stools, carcasses and meat products, and suggested that feces was the most likely source of contamination of the carcasses [3]. The pathogen has also been isolated from environments such as slaughterhouses and sewage, sludge and food-processing plants [4,8,9]. These reports suggest the presence of various sources of L. monocytogenes contamination in the environment.…”
mentioning
confidence: 93%
“…Previous studies have isolated L. monocytogenes from food processing environment [4,9,11]. Animal food products, such as milk, dairy and meat products, have been suggested as especially important infectious sources of the pathogen.…”
mentioning
confidence: 99%
“…While a third lineage (termed lineage III) has been described as including serotypes 4a and 4c, as well as some serotype 4b strains (37,57,59), a recent study indicates the existence of multiple lineages within L. monocytogenes that include isolates with these serotypes (45). Different studies (23,41) have shown that lineage I strains are generally overrepresented among human isolates, while lineage II strains appear to be overrepresented among food isolates (41). Lineage III strains are rare but have been shown to be overrepresented among isolates from animal listeriosis cases (29).…”
mentioning
confidence: 99%
“…En effet, entre 5 et 10°C, la croissance est relativement lente, les taux maximum observés excèdent rarement 100-1000 UFC·g -1 [11]. De plus, le potentiel pathogène de souches de L. monocytogenes isolées du saumon fumé semble faible [37].…”
Section: Origine Et Conséquences De La Contamination Par Listeriaunclassified